Long-term bedaquiline-related treatment outcomes in patients with extensively drug-resistant tuberculosis from South Africa. Issue 5 (31st May 2018) - Olayanju, Olatunde; Limberis, Jason; Esmail, Aliasgar; Oelofse, Suzette; Gina, Phindile; Pietersen, Elize; Fadul, Mohammed; Warren, Rob; Dheda, Keertan
Optimal treatment regimens for patients with extensively drug-resistant tuberculosis (XDR-TB) remain unclear. Long-term prospective outcome data comparing XDR-TB regimens with and without bedaquiline from an endemic setting are lacking. We prospectively followed-up 272 South African patients (49.3% HIV-infected; median CD4 count 169 cells·µL −1 ) with newly diagnosed XDR-TB between 2008 and 2017. Outcomes were compared between those who had not received bedaquiline (pre-2013; n=204) and those who had (post-2013; n=68; 80.9% received linezolid in addition). The 24-month favourable outcome rate was substantially better in the bedaquiline versus the non-bedaquiline group (66.2% (45 out of 68) versus 13.2% (27 out of 204); p<0.001). In addition, the bedaquiline group exhibited reduced 24-month rates of treatment failure (5.9% versus 26.0%; p<0.001) and default (1.5% versus 15.2%; p<0.001). However, linezolid was withdrawn in 32.7% (18 out of 55) of patients in the bedaquiline group because of adverse events. Admission weight >50 kg, an increasing number of anti-TB drugs and bedaquiline were independent predictors of survival (the bedaquiline survival effect remained significant in HIV-infected persons, irrespective of CD4 count). XDR-TB patients receiving a backbone of bedaquiline and linezolid had substantially better favourable outcomes compared to those not using these drugs. These data inform the selection of XDR-TB treatment regimens and roll-out of newer drugs in TB-endemic countries. Bedaquiline remarkably improved treatment-related outcomes in patients with extensively drug-resistant tuberculosis http://ow.ly/lpwG30jsmqK